PENERAPAN ETIKA ADMINISTRASI DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI KANTOR KECAMATAN TAMALANREA KOTA MAKASSAR - Nasir, Nasir (Mimbar Administrasi Mandiri, 2025)
This research is entitled "The Application of Administrative Ethics in Improving the Quality of Public Services at the Tamalanrea District Office, Makassar City". The focus of this research is to evaluate the application of administrative ethics in public services, which includes aspects of equality, justice, loyalty, and responsibility, in order to improve the quality of services to the community. The research method used is qualitative descriptive, with data collection techniques through observation, in-depth interviews, and documentation, involving five informants consisting of sub-district heads, structural officials, and the community. The results of the study show that the application of administrative ethics in the aspects of equality and justice is quite good, reflected in services that refer to SOPs and the absence of discrimination in services to a pluralistic society. The aspect of loyalty is also quite good, although it was found that some employees still face disciplinary obstacles. In terms of responsibility, employees are able to provide fast and appropriate services according to the needs of the community. These findings contribute to the development of public administration ethics, especially in improving the quality of service at the sub-district level as the spearhead of the government.